(untitled) (Research, Society and Development, 2022)
Multisystem Inflammatory Syndrome in Children (MIS-C) is a rare and serious disease associated with the SARS-CoV-2 virus. Clinical manifestations are varied, and evidence of pharmacological treatment is still limited, with the use of anti-inflammatory and immunomodulatory drugs being observed. [Objective] To describe clinical, laboratory, and pharmacological features of a group of children with MIS-C. [Method] Case study of children and adolescents with MIS-C admitted to a university hospital between April and December 2020. The diagnosis and characterization considered the criteria described by the World Health Organization. We followed thechildren from hospital admission until the first three months after discharge. [Results] Twelve children were included in the study, and eleven required admission in a Pediatric Intensive Care Unit (PICU). The median age was eight years. Eight children were male, and eight were declared to be black or brown. All patients had a fever. Other findings were related to abdominal pain (eight children); rash (seven); conjunctivitis (six); vomiting and diarrhea (four). Among the patients admitted to the PICU, five required mechanical ventilation. All received antibiotic therapy. Intravenous immunoglobulin was used in eleven (91.7%) children. The enoxaparin, acetylsalicylic acid and methylprednisolone utilization occurred in eleven, ten, and eight patients, respectively. All children improved after discharge. [Conclusion] There was a predominance of males and black/brown race in this sample. The good clinical, laboratory and echocardiographic evolution with hospital discharge and during the first trimester of follow-up raises favorable hypotheses about the treatments instituted.